Cannibalism by large tadpoles of Rhinophrynus dorsalis (Anura: Rhinophrynidae) - Stynoski, Jennifer Lynn (2018)
In June 2014, we captured approximately 100 R. dorsalis tadpoles in a net from a seasonal wetland in Palo Verde National Park (10.3428 N, 85.3375 W) in N, 85.3375 W) in northwestern Costa Rica. While rearing the tadpoles in the laboratory, we observed five events in which larger tadpoles (Stage 26; Gosner, 1960) fed on conspecifics at earlier stages. At first, we interpreted this behaviour as scavenging. However, after observing more closely during two subsequent events, we noticed that the predated individuals were still alive. We were not able to observe interactions with tadpoles in older stages at this time due to tadpole mortality. Then, during the first week of the rainy season (May to November annually) on 23 May 2018, we collected approximately 300 Rhinophrynus dorsalis tadpoles